2019
DOI: 10.3390/jcm8050735
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Biomarkers for Endometriosis and Endometriosis-Related Ovarian Cancer—An Overview

Abstract: Early detection and accurate diagnosis are pivotal in the management of endometriosis and endometriosis-related ovarian neoplasms (ERONs), yet there is no clear common ground regarding their pathogenesis. Endometriosis is a debilitating pathology that profoundly impairs the quality of life. Although the spontaneous resolution of endometriosis is possible, studies suggest that it can be a progressive condition, and ERONs can develop. The gold standard for diagnosis remains as the invasive method of laparoscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 113 publications
(127 reference statements)
0
33
0
1
Order By: Relevance
“…The incidence of the disease varies between 6-10% [2]. Various sources indicate a constant increase in the number of cases, reaching almost 15% worldwide [3]. Endometriosis is characterized by the migration of endometrial-like cells in ectopic places outside the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of the disease varies between 6-10% [2]. Various sources indicate a constant increase in the number of cases, reaching almost 15% worldwide [3]. Endometriosis is characterized by the migration of endometrial-like cells in ectopic places outside the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al [ 15 ] in a recent meta-analysis comprising a total of 40,609 cases of epithelial ovarian cancer and 368,452 controls from 38 publications, also found that endometriosis was associated with an increased risk of epithelial ovarian cancer (OR = 1.42, 95% CI = 1.28–1.57). Endometriosis and cancer present similarities [ 16 ], such as cell invasion, unrestrained growth, neo-angiogenesis, and decreased apoptosis [ 17 , 18 ], although the first condition is clearly not neoplastic.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial numbers of ncRNAs including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) possess abilities to affect the development and persistence of EMS, unraveling that is of great importance and value to determine novel therapeutic targets and strategies [11]. The miRNAs are a group of short, single-stranded RNAs that control mRNA post-transcriptionally [12].The members of miR-200 family, such as miR-143, 145, miR-20a and miR199a have been reported as the most commonly abnormally expressed miRNAs in EMS [13]. miR-20a is identified as a miRNA that could mediate endothelial and endometrial cell proliferation by inducing fibroblast growth factor-9 [14].…”
Section: Introductionmentioning
confidence: 99%